AL-LAMASÂT AL-BALÂGHIYAH FÎ KITÂB RAFÎQÎ LI MOHAMMAD NUR ASYIQ: DIRÂSAH TAHLÎLIYAH BALÂGHIYAH - Fachrul Ghazi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
Rafiqî by Mohammad Nur Asyiq is one of the literary works which was written in Arabic and was widespread in Indonesia in the seventies. The book is constructed from several Arabic pieces of literatures with the author’s touch of al-Balâghah discipline and its three branches: al-Ma’âny, al-Bayân, and al-Badî’, thus making this book is a suitable candidate for a study concerning al-Balâghah. This book can be used to explore the purpose and intent of applying al-Balâghah language style as well as revealing the scientific and social characteristics of the author. By applying descriptive analytical approach, it was found that the author used several language styles, such as al-Istifhâm, al-Iltifât, al-Qashr, al-Fashl wa al-Washl, at-Tasybîh, al-Kinâyah, and al-Iqtibâs. Those applications of al-Balâgah reveal the author’s noble personality and his affection for Indonesia, his fought against invaders to seize Indonesia’s independence, his eagerness to consume local domestic products, and his compassion for the weak.